Avoidable mortality from respiratory tract infection and sudden unexplained death in children with chronic conditions: a data linkage study - Verfürden, Maximiliane L (Arch Dis Child, 2018)
OBJECTIVE: To determine the risk of death from two potentially avoidable causes with different aetiologies: respiratory tract infection (RTI) and sudden unexplained death (SUD) in children with and without chronic conditions. DESIGN: Whole-country, birth cohort study using linked administrative health databases from Scotland. SETTING AND PARTICIPANTS: Children aged 2 months to less than 5 years in Scotland between 2000 and 2014. MAIN OUTCOME MEASURES: Relative risk of death (expressed as the HR) related to RTIs or SUD, in children with and without chronic conditions. We separately analysed deaths at ages 2–11 months and at 1–4 years and adjusted for birth characteristics, socioeconomic status and vaccination uptake using Cox regression. RESULTS: The cohort comprised 761 172 children. Chronic conditions were recorded in 9.6% (n=72 901) of live births, 82.4% (n=173) of RTI-related deaths and 17.4% (n=49) of SUDs. Chronic conditions were very strongly associated with RTI mortality (2–11 months: HR 68.48, 95% CI (40.57 to 115.60), 1–4 years: HR 38.32, 95% CI (23.26 to 63.14)) and strongly associated with SUD (2–11 months: HR 2.42, 95% CI (1.67 to 3.63), 1–4 years: HR 2.53, 95% CI (1.36 to 4.71)). CONCLUSIONS: The very strong association with chronic conditions suggests that RTI-related mortality may sometimes be a consequence of a terminal decline and not possible to defer or prevent in all cases. Recording whether death was expected on death certificates could indicate which RTI-related deaths might be avoidable through healthcare and public health measures.